A lithium ion battery and its application
By adding additives with specific structures to the electrolyte of lithium-ion batteries, the side reaction problems caused by the reduction of the particle size of the negative electrode material are solved, and the cycle performance and kinetic performance of the battery are improved.
Patent Information
- Application Number
- CN202411536590.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-10-31
AI Technical Summary
In existing lithium-ion batteries, the decrease in the particle size of the negative electrode material leads to an increase in side reactions, affecting circulation and storage performance.
Add additives with specific structures to the electrolyte solution to adjust the relationship between the mass percentage of additives in the electrolyte solution and the particle size parameters of the negative electrode material, inhibit side reactions in ester organic solvents, and reduce the consumption of electrolyte and active lithium.
It realizes reducing the side reaction between the negative electrode material and the electrolyte, reducing the impedance of lithium ions passing through SEI and the negative electrode charge transfer impedance, and improving the cycling and kinetic performance of the battery.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_4
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to a lithium ion battery and its application. Background Art
[0002] As one of the core materials of new energy vehicle power batteries, negative electrode materials play a vital role in the final performance of new energy vehicles. The research on high-performance negative electrode materials has become one of the most active sectors of lithium-ion power batteries. As a core indicator of negative electrode materials, particle size will affect the specific surface area and tap density, thereby affecting the processing technology and rate performance of the battery.
[0003] The particle size of the negative electrode material has a great influence on the electrochemical reaction rate of lithium-ion batteries. The larger the particle size, the longer the diffusion path of lithium ions and electrons in the solid phase, and the slower the electrochemical reaction kinetics; on the contrary, the smaller the negative electrode particle size, the faster the electrochemical reaction kinetics. However, the smaller the negative electrode particle size, the larger the specific surface area of the negative electrode, resulting in more side reactions in the battery and worsening the cycle and storage performance. Therefore, how to solve the side reactions caused by the reduction of the particle size of the negative electrode material is an urgent problem to be solved. Summary of the invention
[0004] The purpose of the present invention is to provide a lithium ion battery and its application. The electrolyte in the lithium ion battery of the present invention can reduce the side reaction between the negative electrode material and the electrolyte, and at the same time can reduce the impedance of lithium ions passing through SEI and the negative electrode charge transfer impedance, so that the electrolyte can match the negative electrode with higher particle size dispersion, and at the same time have excellent cycle performance and kinetic performance.
[0005] The present invention provides a lithium ion battery, comprising a positive electrode, a negative electrode, a separator and an electrolyte;
[0006] The electrolyte comprises an organic solvent, an additive and an electrolyte salt;
[0007] The organic solvent includes a carbonate solvent and / or a carboxylate solvent;
[0008] The additive has a structure shown in Formula I:
[0009]
[0010] In Formula I, R1 is -H or -C n1 H 2n1+1 , R2 is -C n2 H 2n2+1 or -O-(C n2 H 2n2+1 ), R3 is -C n3 H 2n3+1 , n1, n2 and n3 are independently selected from any integer between 1 and 10;
[0011] The mass percentage A% of the additive in the electrolyte and the particle size parameter B of the negative electrode active material satisfy 1.5≤A×B≤90, B=(D90+D10) / D50.
[0012] Preferably, the mass percentage A% of the additive in the electrolyte is 1.5%~30%.
[0013] Preferably, the mass percentage A% of the additive in the electrolyte is 5% to 30%.
[0014] Preferably, 1≤B≤3.
[0015] Preferably, 1.5≤B≤3.
[0016] Preferably, the carbonate solvent includes cyclic carbonate and / or linear carbonate;
[0017] The cyclic carbonates include one or more of ethylene carbonate and its halogenated derivatives, propylene carbonate and its halogenated derivatives, butylene carbonate and its halogenated derivatives, and pentylene carbonate and its halogenated derivatives; the linear carbonates include one or more of dimethyl carbonate and its halogenated derivatives, diethyl carbonate and its halogenated derivatives, dipropyl carbonate and its halogenated derivatives, and ethyl methyl carbonate and its halogenated derivatives;
[0018] The carboxylic acid ester solvent includes one or more of ethyl formate and its halogenated derivatives, ethyl acetate and its halogenated derivatives, ethyl propionate and its halogenated derivatives, and methyl acetate and its halogenated derivatives.
[0019] Preferably, when the carbonate solvent includes cyclic carbonate, the volume percentage F% of the cyclic carbonate in the organic solvent and the mass percentage A% of the additive satisfy 0.1≤A / (A+F)≤0.6.
[0020] Preferably, 15≤F≤45.
[0021] Preferably, 20≤F≤40.
[0022] Preferably, the negative electrode comprises a negative electrode current collector and a negative electrode active material layer composited on the surface of the negative electrode current collector;
[0023] The negative electrode active material layer includes a silicon-containing negative electrode active material;
[0024] The mass percentage C% of silicon in the silicon-containing negative electrode active material, the mass percentage A% of the additive in the electrolyte and the particle size parameter B of the negative electrode material satisfy 0.24≤B×C / A≤12.
[0025] Preferably, the mass percentage C% of silicon in the silicon-containing negative electrode active material is 5% to 30%.
[0026] Preferably, the mass percentage C% of silicon in the silicon-containing negative electrode active material is 8% to 25%.
[0027] Preferably, the positive electrode comprises a positive electrode current collector and a positive electrode active material layer composited on the surface of the positive electrode current collector, the positive electrode active material layer comprises a positive electrode active substance, and the positive electrode active substance is a nickel-cobalt-manganese ternary material, lithium iron phosphate or lithium cobalt oxide.
[0028] The present invention provides the use of the electrolyte in the lithium ion battery as described above in improving the cycle performance of the lithium ion battery while having a high dispersion of the particle size of the negative electrode active material.
[0029] The present invention provides a lithium ion battery, comprising a positive electrode, a negative electrode, a separator and an electrolyte; the electrolyte comprises an organic solvent, an additive and an electrolyte salt; the organic solvent comprises a carbonate solvent and / or a carboxylate solvent; the mass percentage A% of the additive in the electrolyte and the particle size parameter B of the negative electrode material satisfy 1.5≤A×B≤90, B=(D90+D10) / D50. The present invention can suppress the side reactions occurring in the ester organic solvent by adding an additive having a structure shown in formula I to the electrolyte, on the one hand reducing the consumption of the electrolyte and the consumption of active lithium in the battery, and on the other hand achieving the dispersion of the particle size of the negative electrode active material, further improving the cycle capacity retention rate of the battery. DETAILED DESCRIPTION
[0030] The present invention provides a lithium ion battery, comprising a positive electrode, a negative electrode, a separator and an electrolyte;
[0031] The electrolyte comprises an organic solvent, an additive and an electrolyte salt;
[0032] The organic solvent includes a carbonate solvent and / or a carboxylate solvent;
[0033] The additive has a structure shown in Formula I:
[0034]
[0035] In Formula I, R1 is -H or -C n1 H 2n1+1 , R2 is -C n2 H 2n2+1 or -O-(C n2 H 2n2+1 ), R3 is -C n3 H 2n3+1 , n1, n2 and n3 are independently selected from any integer between 1 and 10;
[0036] The mass percentage A% of the additive in the electrolyte and the particle size parameter B of the negative electrode active material satisfy 1.5≤A×B≤90, B=(D90+D10) / D50.
[0037] In the present invention, the organic solvent preferably includes carbonate solvents and / or carboxylate solvents, the carbonate solvents include cyclic carbonates and / or linear carbonates, the cyclic carbonates preferably include one or more of ethylene carbonate and its halogenated derivatives, propylene carbonate and its halogenated derivatives, butylene carbonate and its halogenated derivatives, and pentylene carbonate and its halogenated derivatives; the linear carbonates preferably include one or more of dimethyl carbonate and its halogenated derivatives, diethyl carbonate and its halogenated derivatives, dipropyl carbonate and its halogenated derivatives, and ethyl methyl carbonate and its halogenated derivatives; the carboxylate solvents preferably include one or more of ethyl formate and its halogenated derivatives, ethyl acetate and its halogenated derivatives, ethyl propionate and its halogenated derivatives, and methyl acetate and its halogenated derivatives.
[0038] When lithium-ion batteries are operated in an electrolyte environment containing carbonate solvents and carboxylate solvents, lithium is embedded in the negative electrode of the lithium-ion battery. The lithium-embedded negative electrode will catalyze the carbonate, carboxylate and other solvents in the electrolyte to undergo an ester exchange reaction. The ester exchange reaction is a common reaction in lithium-ion batteries, and ester exchange reactions will occur between carbonate solvents, between carboxylate solvents, and between carbonate and carboxylate. The ester exchange reaction will consume the electrolyte, and the intermediate products generated will trigger new side reactions, resulting in the consumption of active lithium and the reduction of battery capacity, while also creating obstacles to the miniaturization of the particle size of the negative electrode active material.
[0039] However, carbonate solvents and carboxylate solvents are still the most widely used electrolytes in lithium-ion batteries because of their cheapness, availability and stable performance. Therefore, in view of the technical problems existing in the lithium-ion batteries using carbonate solvents and / or carboxylate solvents as the main electrolyte, the present invention adds an additive having a structure shown in Formula I to the electrolyte;
[0040] .
[0041] In Formula I, R1 is -H or -C n1 H 2n1+1 , R2 is -C n2 H 2n2+1 or -O-(C n2 H 2n2+1 ), R3 is -C n3 H 2n3+1, n1, n2 and n3 are independently selected from any integer between 1 and 10, preferably, n1, n2 and n3 are independently selected from 1, 2 or 3; such as R1 is -H or -CH3, R2 is -CH3, -O-CH3 or -O-CH2CH3, and R3 is -CH3 or -CH2CH3.
[0042] Specifically, in some embodiments of the present invention, the additive has a structure shown in Formula I-1 to Formula I-8;
[0043]
[0044] The additive in the present invention is a product of an ester exchange reaction between a lithium ion battery electrolyte solvent, such as a cyclic carbonate solvent and a linear carbonate solvent, and between a cyclic carbonate solvent and a carboxylate solvent. After the additive is added, the ester exchange reaction can be inhibited from continuing to occur, thereby reducing the consumption of the electrolyte and the consumption of active lithium in the battery, and improving the battery's cycle capacity retention rate. Since the added additive needs to play a role in inhibiting the reaction from moving to the right, its addition amount cannot be too low, but the additive in the present invention has a high viscosity, and excessive addition will lead to an increase in electrolyte viscosity, a decrease in electrolyte lithium ion conductivity, and affect the rate performance of the lithium ion battery.
[0045] In the present invention, the mass percentage A% of the additive is preferably 1.5% to 30%, more preferably 5% to 30%, such as 1.5%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, preferably a range value with any of the above values as the upper or lower limit.
[0046] In the present invention, the particle size parameter B of the negative electrode active material = (D90 + D10) / D50. In the prior art, (D90-D10) / D50 represents the concentration of the particle size distribution. In the present application, (D90 + D10) / D50 represented by B represents the dispersion of the particle size distribution. The additives added in the present application can reduce the interface side reaction and improve the negative electrode interface dynamics. Therefore, the particle size distribution of the negative electrode active material does not need to be very concentrated. Under the condition of proper dispersion, the battery can also have good life and dynamic performance. In the present invention, 1≤B≤3, preferably, 1.5≤B≤2.5, such as, B can be 1, 1.2, 1.5, 1.8, 2, 2.2, 2.5, 2.8, 3, preferably a range value with any of the above values as the upper or lower limit.
[0047] In the present invention, the mass percentage A% of the additive in the electrolyte and the particle size parameter B of the negative electrode active material satisfy 1.5≤A×B≤90, more preferably 5≤A×B≤90, preferably, A×B can be 1.5, 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, preferably a range value with any of the above values as the upper or lower limit.
[0048] In the present invention, the particle size of the negative electrode active material has a great influence on the electrochemical reaction rate of the lithium ion battery. The larger the particle size, the longer the diffusion path of lithium ions and electrons in the solid phase, and the slower the electrochemical reaction kinetics; conversely, the smaller the negative electrode particle size, the faster the electrochemical reaction kinetics. In order to improve battery performance, the particle size is usually reduced and a negative electrode material with a smaller particle size is used. However, the specific surface area of the negative electrode will increase when the particle size is reduced, and the side reactions of the negative electrode material and the electrolyte will increase. The main side reaction is the ester exchange reaction of solvents such as carbonates and carboxylates in the electrolyte. Therefore, additives are added to reduce side reactions. Therefore, a balance between additives and particle size must be achieved to effectively improve battery performance.
[0049] In the present invention, the volume percentage F% of the cyclic carbonate in the organic solvent and the mass percentage A% of the additive satisfy 0.1≤A / (A+F)≤0.6, preferably 0.2≤A / (A+F)≤0.5, such as A / (A+F) is 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, preferably a range with any of the above values as the upper or lower limit; wherein 20%≤F%≤40%, preferably 25%≤F%≤35%, such as F% can be 20%, 22%, 25%, 28%, 30%, 32%, 35%, 38%, 40%, preferably a range with any of the above values as the upper or lower limit. The amount of the cyclic carbonate and the additive used within the above range can reduce the side reaction of the electrolyte while ensuring that the electrolyte does not affect the capacity and rate performance of the battery due to the reduction of conductivity.
[0050] In the present invention, the electrolyte salt preferably includes one or more of LiPF6 (lithium hexafluorophosphate), LiFSI (lithium bis(fluorosulfonyl)imide), LiTFSI (lithium bis(trifluoromethylsulfonyl)imide), LiFNFSI (lithium fluorosulfonyl(perfluoro-n-butylsulfonyl)imide), LiTFOP (lithium tetrafluorooxalate phosphate), LiPO2F2 (lithium difluorophosphate), LiODFB (lithium difluorooxalate borate), LiBOB (lithium bis(oxalate borate), LiODFP (lithium difluorobis(oxalate phosphate), LiBF4 (lithium tetrafluoroborate), LiClO4 (lithium perchlorate) and LiAsF6 (lithium hexafluoroarsenate); the mass percentage of the electrolyte salt in the electrolyte is preferably 8% to 20%, more preferably 10% to 15%, such as 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, preferably a range value with any of the above values as the upper or lower limit.
[0051] In the present invention, the negative electrode includes a negative electrode current collector and a negative electrode active material layer composited on the surface of the negative electrode current collector. In the present invention, the negative electrode active material layer preferably includes a silicon-containing negative electrode active material. The silicon negative electrode has a higher capacity, but it also has the problem of easy expansion failure during cycling. The expansion of silicon will cause tension impact on the SEI film on the surface of the negative electrode. Therefore, the greater the silicon content in the negative electrode active material, the higher the film quality requirement for the SEI film on the surface of the negative electrode. Compared with EC-Li + and DMC-Li + Conventional carbonates and Li + The solvation structure of the additive shown in Formula I in the present application and Li + The desolvation structure has a low desolvation energy at the negative electrode potential and can be desolvated quickly; at the same time, the SEI formed by the additive shown in formula I at the negative electrode reduction contains regular OCO bonds, which can quickly react with Li + Complexation-dissociation-complexation is more favorable for Li +By passing through SEI, the probability of side reactions of Li+ on the surface of SEI film can be reduced, and the life of SEI film can be increased to counteract the shortening of life of SEI film due to fatigue during the negative electrode charge and discharge process. Therefore, the electrolyte containing the additive shown in Formula I in the present invention can help increase the silicon content of the negative electrode to increase the energy density of the battery. However, the additive shown in Formula I has a high viscosity. If the additive is added in too much amount, the conductivity of the electrolyte will be reduced, affecting the capacity and rate performance of the battery. Therefore, in the present invention, the mass percentage C% of silicon in the silicon-containing negative electrode active material, the mass percentage A% of the additive in the electrolyte and the particle size parameter B of the negative electrode active material satisfy 0.24≤B×C / A≤12, preferably, 0.5≤B×C / A≤10, such as B×C / A can be 0.24, 0.5, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, preferably with any of the above values as the upper or lower limit of the range value, wherein C% is preferably 5%~30%, more preferably 8%~25%, such as 5%, 10%, 15%, 20%, 25%, 30%, preferably with any of the above values as the upper or lower limit of the range value.
[0052] In the present invention, the expansion of the negative electrode surface may cause the SEI film to crack and expose a new interface, which requires the consumption of active lithium to generate a new SEI film. Therefore, in order to restrict the expansion of the silicon negative electrode and avoid the cracking of the SEI film, the amount of binder added to the silicon negative electrode in the prior art will be higher than that of other graphite negative electrodes. Excessive addition of binder will lead to poor plasticity of the pole piece, and the pole piece is prone to cracking during coating and drying. Cracking will increase the side reaction between the negative electrode and the electrolyte, and consume too much active lithium to reduce the battery capacity; at the same time, consuming too much electrolyte increases the risk of battery diving. It will also reduce the load of the main material and reduce the energy density. The present invention improves the negative electrode film formation and improves the quality of the SEI film by adding the additive shown in Formula I to the electrolyte to reduce the demand for binder. Therefore, by regulating the relationship between A, B, and C to balance the relationship between the energy density and cycle life of the battery, the yield of the pole piece in the production process can also be improved.
[0053] In the present invention, the binder in the silicon-containing negative electrode active material layer is preferably a polyacrylic binder and / or styrene-butadiene latex; the mass percentage of the binder is preferably 0.5% to 3%, more preferably 1.5% to 3%.
[0054] In the present invention, the positive electrode preferably includes a positive electrode current collector and a positive electrode active material layer composited on the surface of the positive electrode current collector, the positive electrode active material layer includes a positive electrode active substance, and the positive electrode active substance is a nickel-cobalt-manganese ternary material, lithium iron phosphate or lithium cobalt oxide. The present invention has no special restrictions on the content of the positive electrode active substance, and it can be set according to the content of the positive electrode active substance commonly used in the art.
[0055] The present invention has no particular limitation on the type of the diaphragm, and any diaphragm commonly used in lithium-ion batteries in the art may be used.
[0056] The present invention also provides a use of the electrolyte containing the compound of formula I as described above in improving the cycle performance of a lithium ion battery while increasing the particle size dispersion of the negative electrode active material.
[0057] The present invention provides a lithium ion battery, comprising a positive electrode, a negative electrode, a separator and an electrolyte; the electrolyte comprises an organic solvent, an additive and an electrolyte salt; the organic solvent comprises a carbonate solvent and / or a carboxylate solvent; the mass percentage A% of the additive in the electrolyte and the particle size parameter B of the negative electrode active material satisfy 1.5≤A×B≤90, B=(D90+D10) / D50. The present invention can suppress the side reactions occurring in the ester organic solvent by adding an additive having a structure shown in formula I to the electrolyte, on the one hand reducing the consumption of the electrolyte and the consumption of active lithium in the battery, on the other hand achieving the dispersion of the particle size of the negative electrode active material, further improving the cycle capacity retention rate of the battery.
[0058] In order to further illustrate the present invention, a lithium ion battery and applications provided by the present invention are described in detail below in conjunction with embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0059] Example 1
[0060] (1) Preparation of positive electrode sheet
[0061] The positive electrode active material LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811), conductive agent acetylene black, and binder PVDF are mixed in a mass ratio of 96:2:2, and solvent NMP is added. The mixture is stirred under the action of a vacuum mixer until the system becomes uniform to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the two surfaces of the positive electrode current collector aluminum foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain a positive electrode sheet.
[0062] (2) Preparation of negative electrode sheet
[0063] A silicon-carbon composite material (the mass ratio of silicon to carbon is 1:1) and an active material graphite are mixed to serve as a negative electrode active material, wherein the D90\D50\D10 of the negative electrode active material are 12 μm, 8.5 μm, and 1.6 μm, respectively;
[0064] The silicon-carbon composite material, graphite, conductive agent acetylene black, binder SBR and PAA are mixed in a mass ratio of 23:73:1:2:1, deionized water is added as a solvent, and stirred under the action of a vacuum mixer until the system is uniform to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on both surfaces of the negative electrode current collector copper foil, dried at room temperature, transferred to an oven for further drying, and then cold pressed and cut to obtain a negative electrode sheet.
[0065] (3) Preparation of electrolyte
[0066] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC) are mixed in a volume ratio of 3:5:2 to obtain an organic solvent. Then, fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L. Then, DMOHC with a mass ratio of 8.5% is added and mixed thoroughly.
[0067] .
[0068] (4) Preparation of isolation membrane
[0069] Polyethylene film is selected as the isolation film.
[0070] (5) Preparation of lithium-ion batteries
[0071] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare battery cell; the bare battery cell is placed in an outer packaging shell, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.
[0072] Example 2
[0073] (1) Preparation of positive electrode sheet
[0074] The positive electrode active material LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811), conductive agent acetylene black, and binder PVDF are mixed in a mass ratio of 96:2:2, and solvent NMP is added. The mixture is stirred under the action of a vacuum mixer until the system becomes uniform to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the two surfaces of the positive electrode current collector aluminum foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain a positive electrode sheet.
[0075] (2) Preparation of negative electrode sheet
[0076] A silicon-carbon composite material (the mass ratio of silicon to carbon is 1:1) and an active material graphite are mixed to serve as a negative electrode active material, wherein the D90\D50\D10 of the negative electrode active material are 13.5 μm, 5 μm, and 1 μm, respectively;
[0077] The silicon-carbon composite material, graphite, conductive agent acetylene black, binder SBR and PAA are mixed in a mass ratio of 23:73:1:2:1, deionized water is added as a solvent, and stirred under the action of a vacuum mixer until the system is uniform to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on both surfaces of the negative electrode collector copper foil, dried at room temperature, transferred to an oven for further drying, and then cold pressed and cut to obtain a negative electrode sheet.
[0078] (3) Preparation of electrolyte
[0079] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC) are mixed in a volume ratio of 3:5:2 to obtain an organic solvent. Then, fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L. Then, 30% by mass of DMOHC is added and mixed thoroughly.
[0080] (4) Preparation of isolation membrane
[0081] A polyethylene film is selected as the separating film.
[0082] (5) Preparation of lithium-ion batteries
[0083] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare battery cell; the bare battery cell is placed in an outer packaging shell, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.
[0084] Example 3
[0085] (1) Preparation of positive electrode sheet
[0086] The positive electrode active material LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811), conductive agent acetylene black, and binder PVDF are mixed in a mass ratio of 96:2:2, and solvent NMP is added. The mixture is stirred under the action of a vacuum mixer until the system becomes uniform to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the two surfaces of the positive electrode current collector aluminum foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain a positive electrode sheet.
[0087] (2) Preparation of negative electrode sheet
[0088] A silicon-carbon composite material (the mass ratio of silicon to carbon is 1:1) and an active material graphite are mixed to serve as a negative electrode active material, wherein the D90\D50\D10 of the negative electrode active material are 8.9 μm, 7.6 μm, and 0.22 μm, respectively;
[0089] The silicon-carbon composite material, graphite, conductive agent acetylene black, binder SBR and PAA are mixed in a mass ratio of 23:73:1:2:1, deionized water is added as a solvent, and stirred under the action of a vacuum mixer until the system is uniform to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on both surfaces of the negative electrode current collector copper foil, dried at room temperature, transferred to an oven for further drying, and then cold pressed and cut to obtain a negative electrode sheet.
[0090] (3) Preparation of electrolyte
[0091] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC) are mixed in a volume ratio of 2:6:2 to obtain an organic solvent. Then, fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L. Then, 1.5% by mass of DMOHC is added and mixed thoroughly.
[0092] (4) Preparation of isolation membrane
[0093] A polyethylene film is selected as the separating film.
[0094] (5) Preparation of lithium-ion batteries
[0095] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare battery cell; the bare battery cell is placed in an outer packaging shell, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.
[0096] Example 4
[0097] (1) Preparation of positive electrode sheet
[0098] The positive electrode active material LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811), conductive agent acetylene black, and binder PVDF are mixed in a mass ratio of 96:2:2, and solvent NMP is added. The mixture is stirred under the action of a vacuum mixer until the system becomes uniform to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the two surfaces of the positive electrode current collector aluminum foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain a positive electrode sheet.
[0099] (2) Preparation of negative electrode sheet
[0100] A silicon-carbon composite material (the mass ratio of silicon to carbon is 1:1) and an active material graphite are mixed to serve as a negative electrode active material, wherein the D90\D50\D10 of the negative electrode active material are 12.5 μm, 6.4 μm, and 0.94 μm, respectively;
[0101] The silicon-carbon composite material, graphite, conductive agent acetylene black, binder SBR and PAA are mixed in a mass ratio of 23:73:1:2:1, deionized water is added as a solvent, and stirred under the action of a vacuum mixer until the system is uniform to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on both surfaces of the negative electrode current collector copper foil, dried at room temperature, transferred to an oven for further drying, and then cold pressed and cut to obtain a negative electrode sheet.
[0102] (3) Preparation of electrolyte
[0103] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC) are mixed in a volume ratio of 3:5:2 to obtain an organic solvent. Then, fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L. Then, 15% by mass of DMOHC is added and mixed thoroughly.
[0104] .
[0105] (4) Preparation of isolation membrane
[0106] A polyethylene film is selected as the separating film.
[0107] (5) Preparation of lithium-ion batteries
[0108] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare battery cell; the bare battery cell is placed in an outer packaging shell, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.
[0109] Example 5
[0110] (1) Preparation of positive electrode sheet
[0111] The positive electrode active material LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811), conductive agent acetylene black, and binder PVDF are mixed in a mass ratio of 96:2:2, and solvent NMP is added. The mixture is stirred under the action of a vacuum mixer until the system becomes uniform to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the two surfaces of the positive electrode current collector aluminum foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain a positive electrode sheet.
[0112] (2) Preparation of negative electrode sheet
[0113] A silicon-carbon composite material (the mass ratio of silicon to carbon is 1:1) and an active material graphite are mixed to serve as a negative electrode active material, wherein the D90\D50\D10 of the negative electrode active material are 10.5 μm, 7.6 μm, and 0.14 μm, respectively;
[0114] The silicon-carbon composite material, graphite, conductive agent acetylene black, binder SBR and PAA are mixed in a mass ratio of 23:73:1:2:1, deionized water is added as a solvent, and stirred under the action of a vacuum mixer until the system is uniform to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on both surfaces of the negative electrode current collector copper foil, dried at room temperature, transferred to an oven for further drying, and then cold pressed and cut to obtain a negative electrode sheet.
[0115] (3) Preparation of electrolyte
[0116] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC) are mixed in a volume ratio of 3:5:2 to obtain an organic solvent. Then, fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L. DMOHC with a mass ratio of 4.2% is added and mixed thoroughly.
[0117] (4) Preparation of isolation membrane
[0118] A polyethylene film is selected as the separating film.
[0119] (5) Preparation of lithium-ion batteries
[0120] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare battery cell; the bare battery cell is placed in an outer packaging shell, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.
[0121] Example 6
[0122] (1) Preparation of positive electrode sheet
[0123] The positive electrode active material LiNi 0.8 Co 0.1 Mn 0.1O2 (NCM811), conductive agent acetylene black, and binder PVDF are mixed in a mass ratio of 96:2:2, and solvent NMP is added. The mixture is stirred under the action of a vacuum mixer until the system becomes uniform to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the two surfaces of the positive electrode current collector aluminum foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain a positive electrode sheet.
[0124] (2) Preparation of negative electrode sheet
[0125] A silicon-carbon composite material (the mass ratio of silicon to carbon is 1:1) and an active material graphite are mixed to serve as a negative electrode active material, wherein the D90\D50\D10 of the negative electrode active material are 10.6 μm, 6.2 μm, and 0.56 μm, respectively;
[0126] The silicon-carbon composite material, graphite, conductive agent acetylene black, binder SBR and PAA are mixed in a mass ratio of 23:73:1:2:1, deionized water is added as a solvent, and stirred under the action of a vacuum mixer until the system is uniform to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on both surfaces of the negative electrode current collector copper foil, dried at room temperature, transferred to an oven for further drying, and then cold pressed and cut to obtain a negative electrode sheet.
[0127] (3) Preparation of electrolyte
[0128] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC) are mixed in a volume ratio of 15:65:20 to obtain an organic solvent. Then, fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L. DMOHC with a mass ratio of 9.8% is added and mixed thoroughly.
[0129] (4) Preparation of isolation membrane
[0130] A polyethylene film is selected as the separating film.
[0131] (5) Preparation of lithium-ion batteries
[0132] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare battery cell; the bare battery cell is placed in an outer packaging shell, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.
[0133] Example 7
[0134] (1) Preparation of positive electrode sheet
[0135] The positive electrode active material LiNi 0.8 Co 0.1 Mn0.1 O2 (NCM811), conductive agent acetylene black, and binder PVDF are mixed in a mass ratio of 96:2:2, and solvent NMP is added. The mixture is stirred under the action of a vacuum mixer until the system becomes uniform to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the two surfaces of the positive electrode current collector aluminum foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain a positive electrode sheet.
[0136] (2) Preparation of negative electrode sheet
[0137] A silicon-carbon composite material (the mass ratio of silicon to carbon is 1:1) and an active material graphite are mixed to serve as a negative electrode active material, wherein the D90\D50\D10 of the negative electrode active material are 10.3 μm, 8.1 μm, and 1.85 μm, respectively;
[0138] The silicon-carbon composite material, graphite, conductive agent acetylene black, binder SBR and PAA are mixed in a mass ratio of 23:73:1:2:1, deionized water is added as a solvent, and stirred under the action of a vacuum mixer until the system is uniform to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on both surfaces of the negative electrode current collector copper foil, dried at room temperature, transferred to an oven for further drying, and then cold pressed and cut to obtain a negative electrode sheet.
[0139] (3) Preparation of electrolyte
[0140] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC) are mixed in a volume ratio of 3:5:2 to obtain an organic solvent. Then, fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L. DMOHC with a mass ratio of 6.5% is added and mixed thoroughly.
[0141] (4) Preparation of isolation membrane
[0142] A polyethylene film is selected as the separating film.
[0143] (5) Preparation of lithium-ion batteries
[0144] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare battery cell; the bare battery cell is placed in an outer packaging shell, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.
[0145] Example 8
[0146] (1) Preparation of positive electrode sheet
[0147] The positive electrode active material LiNi0.8Co0.1Mn0.1O2 (NCM811), the conductive agent acetylene black, and the binder PVDF are mixed in a mass ratio of 96:2:2, and the solvent NMP is added. The mixture is stirred under the action of a vacuum mixer until the system becomes uniform to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the two surfaces of the positive electrode current collector aluminum foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain a positive electrode sheet.
[0148] (2) Preparation of negative electrode sheet
[0149] A silicon-carbon composite material (the mass ratio of silicon to carbon is 1:1) and an active material graphite are mixed to serve as a negative electrode active material, wherein the D90\D50\D10 of the negative electrode active material are 12 μm, 8.5 μm, and 1.6 μm, respectively;
[0150] The silicon-carbon composite material, graphite, conductive agent acetylene black, binder SBR and PAA are mixed in a mass ratio of 58:38:1:2:1, deionized water is added as a solvent, and stirred under the action of a vacuum mixer until the system is uniform to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on both surfaces of the negative electrode collector copper foil, dried at room temperature, transferred to an oven for further drying, and then cold pressed and cut to obtain a negative electrode sheet.
[0151] (3) Preparation of electrolyte
[0152] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC) are mixed in a volume ratio of 3:5:2 to obtain an organic solvent. Then, fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L. Then, 5% by mass of DMOHC is added and mixed thoroughly.
[0153] (4) Preparation of isolation membrane
[0154] A polyethylene film is selected as the separating film.
[0155] (5) Preparation of lithium-ion batteries
[0156] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare battery cell; the bare battery cell is placed in an outer packaging shell, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.
[0157] Example 9
[0158] (1) Preparation of positive electrode sheet
[0159] The positive electrode active material LiNi 0.8 Co0.1 Mn 0.1 O2 (NCM811), conductive agent acetylene black, and binder PVDF are mixed in a mass ratio of 96:2:2, and solvent NMP is added. The mixture is stirred under the action of a vacuum mixer until the system becomes uniform to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the two surfaces of the positive electrode current collector aluminum foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain a positive electrode sheet.
[0160] (2) Preparation of negative electrode sheet
[0161] A silicon-carbon composite material (the mass ratio of silicon to carbon is 1:1) and an active material graphite are mixed to serve as a negative electrode active material, wherein the D90\D50\D10 of the negative electrode active material are 12 μm, 8.5 μm, and 1.6 μm, respectively;
[0162] The silicon-carbon composite material, graphite, conductive agent acetylene black, binder SBR and PAA are mixed in a mass ratio of 9.6:86.4:1:2:1, deionized water is added as a solvent, and stirred under the action of a vacuum mixer until the system is uniform to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on both surfaces of the negative electrode current collector copper foil, dried at room temperature, transferred to an oven for further drying, and then cold pressed and cut to obtain a negative electrode sheet.
[0163] (3) Preparation of electrolyte
[0164] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC) are mixed in a volume ratio of 3:5:2 to obtain an organic solvent. Then, fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L. Then, 30% by mass of DMOHC is added and mixed thoroughly.
[0165] (4) Preparation of isolation membrane
[0166] A polyethylene film is selected as the separating film.
[0167] (5) Preparation of lithium-ion batteries
[0168] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare battery cell; the bare battery cell is placed in an outer packaging shell, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.
[0169] Example 10
[0170] (1) Preparation of positive electrode sheet
[0171] The positive electrode active material LiNi 0.8Co 0.1 Mn 0.1 O2 (NCM811), conductive agent acetylene black, and binder PVDF are mixed in a mass ratio of 96:2:2, and solvent NMP is added. The mixture is stirred under the action of a vacuum mixer until the system becomes uniform to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the two surfaces of the positive electrode current collector aluminum foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain a positive electrode sheet.
[0172] (2) Preparation of negative electrode sheet
[0173] A silicon-carbon composite material (the mass ratio of silicon to carbon is 1:1) and an active material graphite are mixed to serve as a negative electrode active material, wherein the D90\D50\D10 of the negative electrode active material are 12 μm, 8.5 μm, and 1.6 μm, respectively;
[0174] The silicon-carbon composite material, graphite, conductive agent acetylene black, binder SBR and PAA are mixed in a mass ratio of 59.5:36.5:1:2:1, deionized water is added as a solvent, and stirred under the action of a vacuum mixer until the system is uniform to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on both surfaces of the negative electrode collector copper foil, dried at room temperature, transferred to an oven for further drying, and then cold pressed and cut to obtain a negative electrode sheet.
[0175] (3) Preparation of electrolyte
[0176] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC) are mixed in a volume ratio of 3:5:2 to obtain an organic solvent. Then, fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L. Then, DMOHC with a mass ratio of 8.5% is added and mixed thoroughly.
[0177] (4) Preparation of isolation membrane
[0178] A polyethylene film is selected as the separating film.
[0179] (5) Preparation of lithium-ion batteries
[0180] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare battery cell; the bare battery cell is placed in an outer packaging shell, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.
[0181] Embodiment 11
[0182] (1) Preparation of positive electrode sheet
[0183] The positive electrode active material LiNi0.8 Co 0.1 Mn 0.1 O2 (NCM811), conductive agent acetylene black, and binder PVDF are mixed in a mass ratio of 96:2:2, and solvent NMP is added. The mixture is stirred under the action of a vacuum mixer until the system becomes uniform to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the two surfaces of the positive electrode current collector aluminum foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain a positive electrode sheet.
[0184] (2) Preparation of negative electrode sheet
[0185] A silicon-carbon composite material (the mass ratio of silicon to carbon is 1:1) and an active material graphite are mixed to serve as a negative electrode active material, wherein the D90\D50\D10 of the negative electrode active material are 12 μm, 8.5 μm, and 1.6 μm, respectively;
[0186] The silicon-carbon composite material, graphite, conductive agent acetylene black, binder SBR and PAA are mixed in a mass ratio of 8.8:87.2:1:2:1, deionized water is added as a solvent, and stirred under the action of a vacuum mixer until the system is uniform to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on both surfaces of the negative electrode current collector copper foil, dried at room temperature, transferred to an oven for further drying, and then cold pressed and cut to obtain a negative electrode sheet.
[0187] (3) Preparation of electrolyte
[0188] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC) are mixed in a volume ratio of 3:5:2 to obtain an organic solvent. Then, fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L. Then, DMOHC with a mass ratio of 8.5% is added and mixed thoroughly.
[0189] (4) Preparation of isolation membrane
[0190] A polyethylene film is selected as the separating film.
[0191] (5) Preparation of lithium-ion batteries
[0192] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare battery cell; the bare battery cell is placed in an outer packaging shell, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.
[0193] Example 12
[0194] (1) Preparation of positive electrode sheet
[0195] The positive electrode active material LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811), conductive agent acetylene black, and binder PVDF are mixed in a mass ratio of 96:2:2, and solvent NMP is added. The mixture is stirred under the action of a vacuum mixer until the system becomes uniform to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the two surfaces of the positive electrode current collector aluminum foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain a positive electrode sheet.
[0196] (2) Preparation of negative electrode sheet
[0197] A silicon-carbon composite material (the mass ratio of silicon to carbon is 1:1) and an active material graphite are mixed to serve as a negative electrode active material, wherein the D90\D50\D10 of the negative electrode active material are 12 μm, 8.5 μm, and 1.6 μm, respectively;
[0198] The silicon-carbon composite material, graphite, conductive agent acetylene black, binder SBR and PAA are mixed in a mass ratio of 23:73:1:2:1, deionized water is added as a solvent, and stirred under the action of a vacuum mixer until the system is uniform to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on both surfaces of the negative electrode collector copper foil, dried at room temperature, transferred to an oven for further drying, and then cold pressed and cut to obtain a negative electrode sheet.
[0199] (3) Preparation of electrolyte
[0200] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC) are mixed in a volume ratio of 4:4:2 to obtain an organic solvent. Then, fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L. DMOHC with a mass ratio of 8.5% is added and mixed thoroughly.
[0201] (4) Preparation of isolation membrane
[0202] A polyethylene film is selected as the separating film.
[0203] (5) Preparation of lithium-ion batteries
[0204] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare battery cell; the bare battery cell is placed in an outer packaging shell, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.
[0205] Example 13
[0206] (1) Preparation of positive electrode sheet
[0207] The positive electrode active material LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811), conductive agent acetylene black, and binder PVDF are mixed in a mass ratio of 96:2:2, and solvent NMP is added. The mixture is stirred under the action of a vacuum mixer until the system becomes uniform to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the two surfaces of the positive electrode current collector aluminum foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain a positive electrode sheet.
[0208] (2) Preparation of negative electrode sheet
[0209] A silicon-carbon composite material (the mass ratio of silicon to carbon is 1:1) and an active material graphite are mixed to serve as a negative electrode active material, wherein the D90\D50\D10 of the negative electrode active material are 12 μm, 8.5 μm, and 1.6 μm, respectively;
[0210] The silicon-carbon composite material, graphite, conductive agent acetylene black, binder SBR and PAA are mixed in a mass ratio of 23:73:1:2:1, deionized water is added as a solvent, and stirred under the action of a vacuum mixer until the system is uniform to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on both surfaces of the negative electrode collector copper foil, dried at room temperature, transferred to an oven for further drying, and then cold pressed and cut to obtain a negative electrode sheet.
[0211] (3) Preparation of electrolyte
[0212] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC) are mixed in a volume ratio of 2:6:2 to obtain an organic solvent. Then, fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L. DMOHC with a mass ratio of 8.5% is added and mixed thoroughly.
[0213] (4) Preparation of isolation membrane
[0214] A polyethylene film is selected as the separating film.
[0215] (5) Preparation of lithium-ion batteries
[0216] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare battery cell; the bare battery cell is placed in an outer packaging shell, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.
[0217] Embodiment 14
[0218] (1) Preparation of positive electrode sheet
[0219] The positive electrode active material LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811), conductive agent acetylene black, and binder PVDF are mixed in a mass ratio of 96:2:2, and solvent NMP is added. The mixture is stirred under the action of a vacuum mixer until the system becomes uniform to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the two surfaces of the positive electrode current collector aluminum foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain a positive electrode sheet.
[0220] (2) Preparation of negative electrode sheet
[0221] A silicon-carbon composite material (the mass ratio of silicon to carbon is 1:1) and an active material graphite are mixed to serve as a negative electrode active material, wherein the D90\D50\D10 of the negative electrode active material are 12 μm, 8.5 μm, and 1.6 μm, respectively;
[0222] The silicon-carbon composite material, graphite, conductive agent acetylene black, binder SBR and PAA are mixed in a mass ratio of 23:73:1:2:1, deionized water is added as a solvent, and stirred under the action of a vacuum mixer until the system is uniform to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on both surfaces of the negative electrode collector copper foil, dried at room temperature, transferred to an oven for further drying, and then cold pressed and cut to obtain a negative electrode sheet.
[0223] (3) Preparation of electrolyte
[0224] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC) are mixed in a volume ratio of 4.2:3.8:2 to obtain an organic solvent. Then, fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L. Then, DMOHC with a mass ratio of 8.5% is added and mixed thoroughly.
[0225] (4) Preparation of isolation membrane
[0226] A polyethylene film is selected as the separating film.
[0227] (5) Preparation of lithium-ion batteries
[0228] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare battery cell; the bare battery cell is placed in an outer packaging shell, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.
[0229] Embodiment 15
[0230] (1) Preparation of positive electrode sheet
[0231] The positive electrode active material LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811), conductive agent acetylene black, and binder PVDF are mixed in a mass ratio of 96:2:2, and solvent NMP is added. The mixture is stirred under the action of a vacuum mixer until the system becomes uniform to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the two surfaces of the positive electrode current collector aluminum foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain a positive electrode sheet.
[0232] (2) Preparation of negative electrode sheet
[0233] A silicon-carbon composite material (the mass ratio of silicon to carbon is 1:1) and an active material graphite are mixed to serve as a negative electrode active material, wherein the D90\D50\D10 of the negative electrode active material are 12 μm, 8.5 μm, and 1.6 μm, respectively;
[0234] The silicon-carbon composite material, graphite, conductive agent acetylene black, binder SBR and PAA are mixed in a mass ratio of 23:73:1:2:1, deionized water is added as a solvent, and stirred under the action of a vacuum mixer until the system is uniform to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on both surfaces of the negative electrode current collector copper foil, dried at room temperature, transferred to an oven for further drying, and then cold pressed and cut to obtain a negative electrode sheet.
[0235] (3) Preparation of electrolyte
[0236] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC) are mixed in a volume ratio of 1.2:6.8:2 to obtain an organic solvent. Then, fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L. Then, DMOHC with a mass ratio of 8.5% is added and mixed thoroughly.
[0237] (4) Preparation of isolation membrane
[0238] A polyethylene film is selected as the separating film.
[0239] (5) Preparation of lithium-ion batteries
[0240] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare battery cell; the bare battery cell is placed in an outer packaging shell, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.
[0241] Example 16
[0242] (1) Preparation of positive electrode sheet
[0243] The positive electrode active material LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811), conductive agent acetylene black, and binder PVDF are mixed in a mass ratio of 96:2:2, and solvent NMP is added. The mixture is stirred under the action of a vacuum mixer until the system becomes uniform to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the two surfaces of the positive electrode current collector aluminum foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain a positive electrode sheet.
[0244] (2) Preparation of negative electrode sheet
[0245] A silicon-carbon composite material (the mass ratio of silicon to carbon is 1:1) and an active material graphite are mixed to serve as a negative electrode active material, wherein the D90\D50\D10 of the negative electrode active material are 12 μm, 8.5 μm, and 1.6 μm, respectively;
[0246] The silicon-carbon composite material, graphite, conductive agent acetylene black, binder SBR and PAA are mixed in a mass ratio of 23:73:1:2:1, deionized water is added as a solvent, and stirred under the action of a vacuum mixer until the system is uniform to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on both surfaces of the negative electrode current collector copper foil, dried at room temperature, transferred to an oven for further drying, and then cold pressed and cut to obtain a negative electrode sheet.
[0247] (3) Preparation of electrolyte
[0248] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of 3:5:2 to obtain an organic solvent. Then, fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L. DEOHC with a mass ratio of 8.5% is added and mixed thoroughly.
[0249] (4) Preparation of isolation membrane
[0250] A polyethylene film is selected as the separating film.
[0251] (5) Preparation of lithium-ion batteries
[0252] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare battery cell; the bare battery cell is placed in an outer packaging shell, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.
[0253] Embodiment 17
[0254] (1) Preparation of positive electrode sheet
[0255] The positive electrode active material LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811), conductive agent acetylene black, and binder PVDF are mixed in a mass ratio of 96:2:2, and solvent NMP is added. The mixture is stirred under the action of a vacuum mixer until the system becomes uniform to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the two surfaces of the positive electrode current collector aluminum foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain a positive electrode sheet.
[0256] (2) Preparation of negative electrode sheet
[0257] A silicon-carbon composite material (the mass ratio of silicon to carbon is 1:1) and an active material graphite are mixed to serve as a negative electrode active material, wherein the D90\D50\D10 of the negative electrode active material are 12 μm, 8.5 μm, and 1.6 μm, respectively;
[0258] The silicon-carbon composite material, graphite, conductive agent acetylene black, binder SBR and PAA are mixed in a mass ratio of 23:73:1:2:1, deionized water is added as a solvent, and stirred under the action of a vacuum mixer until the system is uniform to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on both surfaces of the negative electrode current collector copper foil, dried at room temperature, transferred to an oven for further drying, and then cold pressed and cut to obtain a negative electrode sheet.
[0259] (3) Preparation of electrolyte
[0260] Propylene carbonate (PC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC) are mixed in a volume ratio of 3:5:2 to obtain an organic solvent. Then, fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L. Then, DMPBC (Formula I-3) with a mass ratio of 8.5% is added and mixed thoroughly.
[0261] (4) Preparation of isolation membrane
[0262] Polyethylene film is selected as the isolation film.
[0263] (5) Preparation of lithium-ion batteries
[0264] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare battery cell; the bare battery cell is placed in an outer packaging shell, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.
[0265] Embodiment 18
[0266] (1) Preparation of positive electrode sheet
[0267] The positive electrode active material LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811), conductive agent acetylene black, and binder PVDF are mixed in a mass ratio of 96:2:2, and solvent NMP is added. The mixture is stirred under the action of a vacuum mixer until the system becomes uniform to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the two surfaces of the positive electrode current collector aluminum foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain a positive electrode sheet.
[0268] (2) Preparation of negative electrode sheet
[0269] A silicon-carbon composite material (the mass ratio of silicon to carbon is 1:1) and an active material graphite are mixed to serve as a negative electrode active material, wherein the D90\D50\D10 of the negative electrode active material are 12 μm, 8.5 μm, and 1.6 μm, respectively;
[0270] The silicon-carbon composite material, graphite, conductive agent acetylene black, binder SBR and PAA are mixed in a mass ratio of 23:73:1:2:1, deionized water is added as a solvent, and stirred under the action of a vacuum mixer until the system is uniform to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on both surfaces of the negative electrode current collector copper foil, dried at room temperature, transferred to an oven for further drying, and then cold pressed and cut to obtain a negative electrode sheet.
[0271] (3) Preparation of electrolyte
[0272] Propylene carbonate (PC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of 3:5:2 to obtain an organic solvent. Then, fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L. Then, 8.5% by mass of DEPBC (Formula I-4) is added and mixed thoroughly.
[0273] (4) Preparation of isolation membrane
[0274] Polyethylene film is selected as the isolation film.
[0275] (5) Preparation of lithium-ion batteries
[0276] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare battery cell; the bare battery cell is placed in an outer packaging shell, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.
[0277] Embodiment 19
[0278] (1) Preparation of positive electrode sheet
[0279] The positive electrode active material LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811), conductive agent acetylene black, and binder PVDF are mixed in a mass ratio of 96:2:2, and solvent NMP is added. The mixture is stirred under the action of a vacuum mixer until the system becomes uniform to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the two surfaces of the positive electrode current collector aluminum foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain a positive electrode sheet.
[0280] (2) Preparation of negative electrode sheet
[0281] A silicon-carbon composite material (the mass ratio of silicon to carbon is 1:1) and an active material graphite are mixed to serve as a negative electrode active material, wherein the D90\D50\D10 of the negative electrode active material are 12 μm, 8.5 μm, and 1.6 μm, respectively;
[0282] The silicon-carbon composite material, graphite, conductive agent acetylene black, binder SBR and PAA are mixed in a mass ratio of 23:73:1:2:1, deionized water is added as a solvent, and stirred under the action of a vacuum mixer until the system is uniform to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on both surfaces of the negative electrode current collector copper foil, dried at room temperature, transferred to an oven for further drying, and then cold pressed and cut to obtain a negative electrode sheet.
[0283] (3) Preparation of electrolyte
[0284] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and ethyl acetate (EA) are mixed in a volume ratio of 3:5:2 to obtain an organic solvent. Then, fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L. Then, 8.5% by mass of ECOEA (Formula I-5) is added and mixed thoroughly.
[0285] (4) Preparation of isolation membrane
[0286] Polyethylene film is selected as the isolation film.
[0287] (5) Preparation of lithium-ion batteries
[0288] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare battery cell; the bare battery cell is placed in an outer packaging shell, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.
[0289] Embodiment 20
[0290] (1) Preparation of positive electrode sheet
[0291] The positive electrode active material LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811), conductive agent acetylene black, and binder PVDF are mixed in a mass ratio of 96:2:2, and solvent NMP is added. The mixture is stirred under the action of a vacuum mixer until the system becomes uniform to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the two surfaces of the positive electrode current collector aluminum foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain a positive electrode sheet.
[0292] (2) Preparation of negative electrode sheet
[0293] A silicon-carbon composite material (the mass ratio of silicon to carbon is 1:1) and an active material graphite are mixed to serve as a negative electrode active material, wherein the D90\D50\D10 of the negative electrode active material are 12 μm, 8.5 μm, and 1.6 μm, respectively;
[0294] The silicon-carbon composite material, graphite, conductive agent acetylene black, binder SBR and PAA are mixed in a mass ratio of 23:73:1:2:1, deionized water is added as a solvent, and stirred under the action of a vacuum mixer until the system is uniform to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on both surfaces of the negative electrode current collector copper foil, dried at room temperature, transferred to an oven for further drying, and then cold pressed and cut to obtain a negative electrode sheet.
[0295] (3) Preparation of electrolyte
[0296] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and methyl acetate (MA) are mixed in a volume ratio of 3:5:2 to obtain an organic solvent. Then, fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L. Then, MCOEA (Formula I-6) with a mass ratio of 8.5% is added and mixed thoroughly.
[0297] (4) Preparation of isolation membrane
[0298] Polyethylene film is selected as the isolation film.
[0299] (5) Preparation of lithium-ion batteries
[0300] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare battery cell; the bare battery cell is placed in an outer packaging shell, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.
[0301] Embodiment 21
[0302] (1) Preparation of positive electrode sheet
[0303] The positive electrode active material LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811), conductive agent acetylene black, and binder PVDF are mixed in a mass ratio of 96:2:2, and solvent NMP is added. The mixture is stirred under the action of a vacuum mixer until the system becomes uniform to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the two surfaces of the positive electrode current collector aluminum foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain a positive electrode sheet.
[0304] (2) Preparation of negative electrode sheet
[0305] A silicon-carbon composite material (the mass ratio of silicon to carbon is 1:1) and an active material graphite are mixed to serve as a negative electrode active material, wherein the D90\D50\D10 of the negative electrode active material are 12 μm, 8.5 μm, and 1.6 μm, respectively;
[0306] The silicon-carbon composite material, graphite, conductive agent acetylene black, binder SBR and PAA are mixed in a mass ratio of 23:73:1:2:1, deionized water is added as a solvent, and stirred under the action of a vacuum mixer until the system is uniform to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on both surfaces of the negative electrode current collector copper foil, dried at room temperature, transferred to an oven for further drying, and then cold pressed and cut to obtain a negative electrode sheet.
[0307] (3) Preparation of electrolyte
[0308] Propylene carbonate (PC), ethyl methyl carbonate (EMC) and methyl acetate (MA) are mixed in a volume ratio of 3:5:2 to obtain an organic solvent. Then, fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L. Then, DEPBC (Formula I-7) with a mass ratio of 8.5% is added and mixed thoroughly.
[0309] (4) Preparation of isolation membrane
[0310] Polyethylene film is selected as the isolation film.
[0311] (5) Preparation of lithium-ion batteries
[0312] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare battery cell; the bare battery cell is placed in an outer packaging shell, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.
[0313] Embodiment 22
[0314] (1) Preparation of positive electrode sheet
[0315] The positive electrode active material LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811), conductive agent acetylene black, and binder PVDF are mixed in a mass ratio of 96:2:2, and solvent NMP is added. The mixture is stirred under the action of a vacuum mixer until the system becomes uniform to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the two surfaces of the positive electrode current collector aluminum foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain a positive electrode sheet.
[0316] (2) Preparation of negative electrode sheet
[0317] A silicon-carbon composite material (the mass ratio of silicon to carbon is 1:1) and an active material graphite are mixed to serve as a negative electrode active material, wherein the D90\D50\D10 of the negative electrode active material are 12 μm, 8.5 μm, and 1.6 μm, respectively;
[0318] The silicon-carbon composite material, graphite, conductive agent acetylene black, binder SBR and PAA are mixed in a mass ratio of 23:73:1:2:1, deionized water is added as a solvent, and stirred under the action of a vacuum mixer until the system is uniform to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on both surfaces of the negative electrode current collector copper foil, dried at room temperature, transferred to an oven for further drying, and then cold pressed and cut to obtain a negative electrode sheet.
[0319] (3) Preparation of electrolyte
[0320] Propylene carbonate (PC), ethyl methyl carbonate (EMC) and ethyl acetate (EA) are mixed in a volume ratio of 3:5:2 to obtain an organic solvent. Then, fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L. Then, 8.5% by mass of DEPBC (Formula I-8) is added and mixed thoroughly.
[0321] (4) Preparation of isolation membrane
[0322] Polyethylene film is selected as the isolation film.
[0323] (5) Preparation of lithium-ion batteries
[0324] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare battery cell; the bare battery cell is placed in an outer packaging shell, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.
[0325] Comparative Example 1
[0326] (1) Preparation of positive electrode sheet
[0327] The positive electrode active material LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811), conductive agent acetylene black, and binder PVDF are mixed in a mass ratio of 96:2:2, and solvent NMP is added. The mixture is stirred under the action of a vacuum mixer until the system becomes uniform to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the two surfaces of the positive electrode current collector aluminum foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain a positive electrode sheet.
[0328] (2) Preparation of negative electrode sheet
[0329] A silicon-carbon composite material (the mass ratio of silicon to carbon is 1:1) and an active material graphite are mixed to serve as a negative electrode active material, wherein the D90\D50\D10 of the negative electrode active material are 14.2 μm, 5 μm, and 0.8 μm, respectively;
[0330] The silicon-carbon composite material, graphite, conductive agent acetylene black, binder SBR and PAA are mixed in a mass ratio of 59.5:36.5:1:2:1, deionized water is added as a solvent, and stirred under the action of a vacuum mixer until the system is uniform to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on both surfaces of the negative electrode current collector copper foil, dried at room temperature, transferred to an oven for further drying, and then cold pressed and cut to obtain a negative electrode sheet.
[0331] (3) Preparation of electrolyte
[0332] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of 4.3:3.7:2 to obtain an organic solvent. Then, fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L. DMOHC with a mass ratio of 32% is added and mixed thoroughly.
[0333] (4) Preparation of isolation membrane
[0334] A polyethylene film is selected as the separating film.
[0335] (5) Preparation of lithium-ion batteries
[0336] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare battery cell; the bare battery cell is placed in an outer packaging shell, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.
[0337] Comparative Example 2
[0338] (1) Preparation of positive electrode
[0339] The positive electrode active material LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811), conductive agent acetylene black, and binder PVDF are mixed in a mass ratio of 96:2:2, and solvent NMP is added. The mixture is stirred under the action of a vacuum mixer until the system becomes uniform to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the two surfaces of the positive electrode current collector aluminum foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain a positive electrode sheet.
[0340] (2) Preparation of negative electrode sheet
[0341] A silicon-carbon composite material (the mass ratio of silicon to carbon is 1:1) and an active material graphite are mixed to serve as a negative electrode active material, wherein the D90\D50\D10 of the negative electrode active material are 12.5 μm, 11.5 μm, and 0.15 μm, respectively;
[0342] The silicon-carbon composite material, graphite, conductive agent acetylene black, binder SBR and PAA are mixed in a mass ratio of 8.8:87.2:1:2:1, deionized water is added as a solvent, and stirred under the action of a vacuum mixer until the system is uniform to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on both surfaces of the negative electrode current collector copper foil, dried at room temperature, transferred to an oven for further drying, and then cold pressed and cut to obtain a negative electrode sheet.
[0343] (3) Preparation of electrolyte
[0344] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of 1.6:6.4:2 to obtain an organic solvent. Then, fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L. Then, DMOHC with a mass ratio of 1.2% is added and mixed thoroughly.
[0345] (4) Preparation of isolation membrane
[0346] A polyethylene film is selected as the separating film.
[0347] (5) Preparation of lithium-ion batteries
[0348] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare battery cell; the bare battery cell is placed in an outer packaging shell, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.
[0349] Comparative Example 3
[0350] (1) Preparation of positive electrode
[0351] The positive electrode active material LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811), conductive agent acetylene black, and binder PVDF are mixed in a mass ratio of 96:2:2, and solvent NMP is added. The mixture is stirred under the action of a vacuum mixer until the system becomes uniform to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the two surfaces of the positive electrode current collector aluminum foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain a positive electrode sheet.
[0352] (2) Preparation of negative electrode sheet
[0353] A silicon-carbon composite material (the mass ratio of silicon to carbon is 1:1) and an active material graphite are mixed to serve as a negative electrode active material, wherein the D90\D50\D10 of the negative electrode active material are 14.2 μm, 5 μm, and 0.8 μm, respectively;
[0354] The silicon-carbon composite material, graphite, conductive agent acetylene black, binder SBR and PAA are mixed in a mass ratio of 59.5:36.5:1:0.25:2.75, deionized water is added as a solvent, and stirred under the action of a vacuum mixer until the system is uniform to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on both surfaces of the negative electrode current collector copper foil, dried at room temperature, transferred to an oven for further drying, and then cold pressed and cut to obtain a negative electrode sheet.
[0355] (3) Preparation of electrolyte
[0356] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of 4.2:3.8:2 to obtain an organic solvent. Then, fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L. DEOHC with a mass ratio of 31% is added and mixed thoroughly.
[0357] (4) Preparation of isolation membrane
[0358] A polyethylene film is selected as the separating film.
[0359] (5) Preparation of lithium-ion batteries
[0360] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare battery cell; the bare battery cell is placed in an outer packaging shell, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.
[0361] Comparative Example 4
[0362] (1) Preparation of positive electrode
[0363] The positive electrode active material LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811), conductive agent acetylene black, and binder PVDF are mixed in a mass ratio of 96:2:2, and solvent NMP is added. The mixture is stirred under the action of a vacuum mixer until the system becomes uniform to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the two surfaces of the positive electrode current collector aluminum foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain a positive electrode sheet.
[0364] (2) Preparation of negative electrode sheet
[0365] A silicon-carbon composite material (the mass ratio of silicon to carbon is 1:1) and an active material graphite are mixed to serve as a negative electrode active material, wherein the D90\D50\D10 of the negative electrode active material are 12.5 μm, 11.5 μm, and 0.15 μm, respectively;
[0366] The silicon-carbon composite material, graphite, conductive agent acetylene black, binder SBR and PAA are mixed in a mass ratio of 8.8:87.2:1:2.8:0.2, deionized water is added as a solvent, and stirred under the action of a vacuum mixer until the system is uniform to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on both surfaces of the negative electrode collector copper foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain a negative electrode sheet.
[0367] (3) Preparation of electrolyte
[0368] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of 1.5:6.5:2 to obtain an organic solvent. Then, fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L. Then, 1.3% by mass of DEOHC is added and mixed thoroughly.
[0369] (4) Preparation of isolation membrane
[0370] A polyethylene film is selected as the separating film.
[0371] (5) Preparation of lithium-ion batteries
[0372] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare battery cell; the bare battery cell is placed in an outer packaging shell, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.
[0373] Comparative Example 5
[0374] (1) Preparation of positive electrode
[0375] The positive electrode active material LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811), conductive agent acetylene black, and binder PVDF are mixed in a mass ratio of 96:2:2, and solvent NMP is added. The mixture is stirred under the action of a vacuum mixer until the system becomes uniform to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the two surfaces of the positive electrode current collector aluminum foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain a positive electrode sheet.
[0376] (2) Preparation of negative electrode sheet
[0377] A silicon-carbon composite material (the mass ratio of silicon to carbon is 1:1) and an active material graphite are mixed to serve as a negative electrode active material, wherein the D90\D50\D10 of the negative electrode active material are 12 μm, 8.5 μm, and 1.6 μm, respectively;
[0378] The silicon-carbon composite material, graphite, conductive agent acetylene black, binder SBR and PAA are mixed in a mass ratio of 23:73:1:2:1, deionized water is added as a solvent, and stirred under the action of a vacuum mixer until the system is uniform to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on both surfaces of the negative electrode collector copper foil, dried at room temperature, transferred to an oven for further drying, and then cold pressed and cut to obtain a negative electrode sheet.
[0379] (3) Preparation of electrolyte
[0380] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of 3:5:2 to obtain an organic solvent. Then, fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L. Then, FEC with a mass ratio of 8.5% is added and mixed thoroughly.
[0381] (4) Preparation of isolation membrane
[0382] A polyethylene film is selected as the separating film.
[0383] (5) Preparation of lithium-ion batteries
[0384] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare battery cell; the bare battery cell is placed in an outer packaging shell, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.
[0385] The performance of the batteries in the examples and comparative examples was tested according to the following method. The results are shown in Table 1.
[0386] 1) Quantitative testing methods for solvents (EC, DEC, DMC) and additives (DMOHC / DEOHC) in electrolytes;
[0387] Use battery charging and discharging equipment to discharge the battery. Discharging conditions: current 0.3C, cut-off voltage 2.0V. After recording the battery number / barcode, disassemble the battery in a glove box (H2O≤0.1ppm, O2≤0.1ppm) to collect the electrolyte. There are three ways to collect the electrolyte: After removing the battery cover, ① If there is free electrolyte, use a pipette to collect the electrolyte into a 5mL sample tube and seal it with sealing glue to prevent electrolyte leakage. ② If there is no free electrolyte, use a hydraulic press (Beijing Hengaode Technology Co., Ltd. FY-30 hydraulic press) to continuously pressurize until free electrolyte appears, collect the electrolyte into the sample tube and seal it. ③ Alternatively, add an appropriate amount of dichloromethane extractant to the battery and record the dichloromethane content. After adding dichloromethane, put the battery into an aluminum-plastic bag and seal it with a heat sealer. Transfer it to an ultrasonic oscillator and oscillate it for 12 hours to allow the electrolyte in the electrode to be fully mixed with dichloromethane. Then use a pipette to draw the mixture of dichloromethane and electrolyte into a 5mL sample tube and seal the sample tube with sealing glue; inject the collected electrolyte sample into the Agilent Intuvo 9000 gas chromatograph with a microinjector to test the electrolyte composition, and give the concentration of each component in the electrolyte by comparing with the standard database.
[0388] 4) Test method for interface impedance of positive and negative electrodes in batteries;
[0389] Use the battery charging and discharging equipment to adjust the battery to 50% SOC, specifically: use 0.3C current to charge and discharge three times to fix the capacity, 0.3C to fully charge, and 0.3C to discharge until the capacity reaches 50% of the third discharge capacity of the fixed capacity. Remove the battery from the charging and discharging equipment, wrap the pole ear with insulating glue, transfer it to the glove box (H2O≤0.1ppm, O2≤0.1ppm), disassemble the battery, and place the positive and negative electrodes in a polytetrafluoroethylene box containing DMC for cleaning. After cleaning, take out the electrodes and dry them naturally, and then use a punching machine to cut the positive and negative electrodes into 9mm diameter discs and seal them in self-sealing bags. Use the above-cut positive and negative electrodes and diaphragms to assemble symmetrical batteries. Symmetrical positive battery assembly: assemble button symmetrical positive battery in the order of positive electrode sheet, electrolyte, PP separator, electrolyte, positive electrode sheet; Symmetrical negative battery assembly: assemble button symmetrical negative battery in the order of negative electrode sheet, electrolyte, PP separator, electrolyte, negative electrode sheet. After the assembled symmetrical positive and symmetrical negative batteries were left at room temperature for 24 hours, the AC impedance of the symmetrical positive and symmetrical negative batteries was tested using a CS310X multi-channel electrochemical workstation, with an amplitude of 5mV and a frequency of 100000-0.1Hz.
[0390] 5) Electrolyte ion conductivity test method;
[0391] The ionic conductivity of the electrolyte is tested using a Mettler S230-K conductivity meter. The conductivity meter consists of a conductivity electrode and an electronic unit. It uses high-frequency alternating current to measure the resistance of the solution between two parallel electrodes. The electronic unit uses an alternating current signal of appropriate frequency to amplify the signal and convert it into conductivity. The test steps are as follows: :
[0392] 1. Electrode calibration
[0393] Take about 10mL of 12.88mS / cm conductivity standard solution and place it in a centrifuge tube. Soak it in a water bath at 25℃ for 30min. When the temperature of the conductivity standard solution measured by the temperature electrode is 25.0±0.2℃, start calibration. If the conductivity test result of the standard solution is 12.88±0.15mS / cm, the calibration is successful.
[0394] 2. Sample Preparation
[0395] Take about 100 mL of sample from a clean, dry fluorinated bottle, seal it, and place the sample in a constant temperature water bath at 25.0±0.2℃ for 30 minutes.
[0396] 3. Testing
[0397] Install the conductivity electrode and clean it with ethanol, then wipe it dry with filter paper; open the sampling bottle, immerse the conductivity electrode in the sample to be tested, select "automatic measurement mode", click the "measurement" button to start measuring, and after hearing the "beeping" sound, the value does not change, record the current value, which is the conductivity.
[0398] 6) Testing method for silicon content in negative electrode sheets;
[0399] Pole processing method:
[0400] ① Disassembly: Take the sample to be tested with a 0% charge state and disassemble it, package and preserve the negative electrode sheet and bring it back to the laboratory for processing;
[0401] ② Treatment: The battery to be tested is charged to 0% SOC state, the electrode is disassembled and immersed in DMC for 48 hours, and the DMC is replaced every 24 hours. The cleaned electrode is baked to remove the residual DMC solvent to obtain the electrode to be tested.
[0402] ③Test: CP is the use of argon ion beam to polish the cross section of the sample. The principle is as follows: a high-voltage electric field is used to ionize argon gas to produce an ion state. The generated argon ions bombard the surface of the silicon-carbon material at high speed under the action of the accelerating voltage, and the sample is etched layer by layer to achieve the polishing effect. The same electrode to be tested is cut with CP, and 4 sections are obtained. Each section is scanned by SEM, and 4 fields of view are selected for surface scanning at 500 times. Surface scanning is the electron beam irradiating the sample to produce characteristic X-rays; by detecting and analyzing X-rays, a spectrum distributed according to the energy size of the X-rays can be obtained, thereby analyzing the element ratio, and finally the average value of all values of the silicon content obtained by surface scanning of 16 fields of view of 4 sections is taken as the most accurate conclusion.
[0403] 9) Battery cycle test method.
[0404] The LAND system was used to test the cycle performance of lithium-ion batteries. The lithium-ion batteries were charged and discharged for 1000 cycles at a charge and discharge rate of 0.5C / 1C, a current cutoff of 0.05C, and a voltage range of 2.5-4.25V. After the cycle, the cycle data was processed to obtain the capacity retention rate (the discharge capacity of the first cycle divided by the discharge capacity of each cycle is the capacity retention rate), and the capacity retention rate of the battery after 1000 cycles was obtained.
[0405] Table 1 Performance data of batteries in examples and comparative examples
[0406]
[0407] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A lithium ion battery comprising a positive electrode, a negative electrode, a separator and an electrolyte; The electrolyte comprises an organic solvent, an additive and an electrolyte salt; The organic solvent comprises a combination of a cyclic carbonate solvent and a linear carbonate solvent, or a combination of a cyclic carbonate solvent and a carboxylic acid ester solvent, or a combination of a cyclic carbonate solvent, a linear carbonate solvent and a carboxylic acid ester solvent; The additive has a structure shown in Formula I: In Formula I, R1 is -H or -C n1 H 2n1+1 , R2 is -C n2 H 2n2+1 or -O-(C n2 H 2n2+1 ), R3 is -C n3 H 2n3+1 , n1, n2 and n3 are independently selected from any integer between 1 and 10; The mass percentage A% of the additive in the electrolyte is 7% to 30%; The volume percentage F% of the cyclic carbonate in the organic solvent and the mass percentage A% of the additive satisfy 0.1≤A / (A+F)≤0.6; The negative electrode comprises a negative electrode current collector and a negative electrode active material layer composited on the surface of the negative electrode current collector; The negative electrode active material layer includes a silicon-containing negative electrode active material; The mass percentage C% of silicon in the silicon-containing negative electrode active material is 5% to 30%.
2. The lithium-ion battery according to claim 1, characterized in that The cyclic carbonates include one or more of ethylene carbonate and its halogenated derivatives, propylene carbonate and its halogenated derivatives, butylene carbonate and its halogenated derivatives, and pentylene carbonate and its halogenated derivatives; the linear carbonates include one or more of dimethyl carbonate and its halogenated derivatives, diethyl carbonate and its halogenated derivatives, dipropyl carbonate and its halogenated derivatives, and ethyl methyl carbonate and its halogenated derivatives; The carboxylic acid ester solvent includes one or more of ethyl formate and its halogenated derivatives, ethyl acetate and its halogenated derivatives, ethyl propionate and its halogenated derivatives, and methyl acetate and its halogenated derivatives.
3. The lithium-ion battery according to claim 1, characterized in that 15≤F≤45。 4. The lithium-ion battery according to claim 3, characterized in that: 20≤F≤40。 5. The lithium-ion battery according to claim 1, characterized in that: The mass percentage C% of silicon in the silicon-containing negative electrode active material is 8% to 25%.
6. The lithium-ion battery according to claim 1, characterized in that The positive electrode comprises a positive electrode current collector and a positive electrode active material layer composited on the surface of the positive electrode current collector, the positive electrode active material layer comprises a positive electrode active substance, and the positive electrode active substance is a nickel-cobalt-manganese ternary material, lithium iron phosphate or lithium cobalt oxide.
Citation Information
Patent Citations
Carbonate compounds for energy storage device electrolyte compositions, and methods thereof
WO2023240191A1